Adalimumab for Ocular Inflammation. (4th May 2017) - Durrani, Khayyam; Kempen, John H.; Ying, Gui-shuang; Kacmaz, R. Oktay; Artornsombudh, Pichaporn; Rosenbaum, James T.; Suhler, Eric B.; Thorne, Jennifer E.; Jabs, Douglas A.; Levy-Clarke, Grace A.; Nussenblatt, Robert B.; Foster, C. Stephen; et al.
ABSTRACT: Purpose : To evaluate adalimumab as an immunomodulatory treatment for non-infectious ocular inflammatory diseases. Methods : Characteristics of patients treated with adalimumab were abstracted in a standardized chart review. Main outcomes measured were control of inflammation, corticosteroid-sparing effect, and visual acuity. Results : In total, 32 patients with ocular inflammation were treated with adalimumab. The most common ophthalmic diagnoses were anterior uveitis, occurring in 15 patients (47%), and scleritis, occurring in 9 patients (28%). At 6 months of therapy, among 15 eyes with active inflammation, 7 (47%) became completely inactive, and oral prednisone was reduced to ≤10 mg/day in 2 of 4 patients (50%). On average, visual acuity decreased by 0.13 lines during the first 6 months of treatment. Adalimumab was discontinued because of lack of effectiveness in four patients within 6 months. Conclusions : Adalimumab was moderately effective in controlling inflammation in a group of highly pre-treated cases of ocular inflammatory disease.